2023
DOI: 10.3390/biomimetics8010125
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualization of Biomimicry in Engineering Context among Undergraduate and High School Students: An International Interdisciplinary Exploration

Abstract: Biomimicry is an interdisciplinary design approach that provides solutions to engineering problems by taking inspiration from nature. Given the established importance of biomimicry for building a sustainable world, there is a need to develop effective curricula on this topic. In this study, a workshop was conducted twice in Singapore: once with 14 students from a local high school in Singapore, and once with 11 undergraduate students in engineering from the United States. The workshop aimed to better understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In other studies, it has been found that the biomimicry class stimulates curiosity and motivation, making learning an active and enjoyable experience. On the other hand, research has shown that students often make unnecessary connections and struggle to involve all participants [58].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, it has been found that the biomimicry class stimulates curiosity and motivation, making learning an active and enjoyable experience. On the other hand, research has shown that students often make unnecessary connections and struggle to involve all participants [58].…”
Section: Discussionmentioning
confidence: 99%
“…Biomimicry has the potential to transform the majority of domestic and international economies, making it possible to achieve both economic growth and environmental goals simultaneously [ 2 , 3 ]. Although the commercial application of biomimicry is still irregular, several well-known achievements, such as Shinkansen and Velcro, demonstrate the potential of biomimicry [ 4 , 5 , 6 ]. The public’s awareness of patents related to bio-inspired and biomimetics likely arose when it was revealed that the roof design of the Crystal Palace in London, United Kingdom, was bio-inspired by the functionality of the leaf of a water lily, specifically its ability to support substantial weight in water [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this projectbased learning, the student's competencies and skills were significantly enhanced, which was thought to benefit them in their future careers. Furthermore, a study about biomimicry, an interdisciplinary design thinking approach that answers engineering issues by taking inspiration from nature, explored the understanding and perceptions of biomimicry among undergraduate and high school students from different countries [40]. The findings revealed that students had limited knowledge of its applications in engineering and required more assistance in developing their ideas into prototypes using a top-down approach, also referred to as problem-driven method or indirect biomimicry that involves using biological systems as a model to design new prototypes, which reflects the pertinence of DT in education.…”
Section: Design Thinking In Educationmentioning
confidence: 99%